Penguatan Literasi Bahasa dan Digitalisasi Dakwah Berbasis Pesantren - Nurul Aini; Siti Amsariah; Eny Maulita Purnama Sari; Ariyani Etik Kurniasari; Cholida Nur Fajri; Fatoni Dwi Atmoko; Dwi Utami; Hadziq Qulubi (Universitas Lampung, 2025)
The rapid development of digital technology has significantly changed communication patterns in society, including Islamic da'wah practices. Islamic boarding schools, as centers of Islamic literacy, play a strategic role in responding to these changes to ensure that da'wah remains relevant, ethical, and rooted in Islamic values. This community service activity aims to strengthen language literacy and improve students' understanding of digital da'wah based on Islamic boarding schools. This activity was carried out in the form of academic discussions at the Minhajur Rufaqo Islamic Boarding School, Taman Fajar, East Lampung, involving students and university students. The methods used included interactive lectures, discussions, and individual brainstorming. The results showed an increase in participants' understanding of the characteristics of digital da'wah, the importance of using polite and persuasive language, and the role of students as responsible agents of digital da'wah. In addition, participants came up with creative ideas for utilizing digital media as a means of pesantren da'wah. This activity contributed to the development of an adaptive, ethical, and sustainable pesantren-based digital da'wah model.